Open study of short course Fleroxacin for Typhoid and Paratyphoid Fever (Faculty of Medicine Universitas Indonesia, 2002)
The objective of this study was to evaluate clinical and bacteriological effect of short course fleroxacin in uncomplicated typhoid and paratyphoid fever patients. Four hundred mg of fleroxacin was given oraly once daily for a period of 3 to 5 days. The diagnosis of typhoid and paratyphoid fever was established by clinical picture as well as blood culture or Widal serology test. Thirty patients in whom the clinical picture was confirmed as a typhoid or paratyphoid infection were eligible for this investigation. They consisted of 15 males and 15 females ranging in age from 18-38 years average 27.5 years of whom 18 were diagnosed by blood culture consisting of 16 S.typhi positive cases and two S.paratyphi A, while 12 other cases were positively confirmed by serial Widal agglutination serology. These cases suffered from fever between 3-14 days with a minimum recorded body temperature elevation of 38.5 degrees Celsius. Clinical response with defervescence of fever was obtained in the positive blood culture group within 3 days (8 patients) including 2 cases positive for S.paratyphi A and within two additional days (5 days) in the remaining 10 cases. In the twelve cases with a positive serology for typhoid fever a clinical response was obtained for defervescence within 3 days (6 cases) with 4 of these cases were on 3 days of fleroxacin and 2 cases on 5 days of fleroxacin. In the remaining 6 serologic positive cases fever resolved after 4-6 days with an average of 5 days with one on 3 days of fleroxacin and the rest (5 cases) on 5 days of fleroxacin. All positive blood culture cases reverted to negative after the fleroxacin course. No relapse or carrier state was recorded in this serie. It may be concluded that a 3 to 5 days closely monitored course of fleroxacin has excellent clinical as well as bacteriological efficacy in noncomplicated typhoid and paratyphoid fever. (Med J Indones 2002; 11: 41-7)Keywords: fluoroquinolones, enteric infections, short course efficacy, open prospective study